2023
DOI: 10.1007/s40820-023-01081-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Porous-Reinforcement Microstructure-Based Flexible Triboelectric Patch for Remote Healthcare

Abstract: Realizing real-time monitoring of physiological signals is vital for preventing and treating chronic diseases in elderly individuals. However, wearable sensors with low power consumption and high sensitivity to both weak physiological signals and large mechanical stimuli remain challenges. Here, a flexible triboelectric patch (FTEP) based on porous-reinforcement microstructures for remote health monitoring has been reported. The porous-reinforcement microstructure is constructed by the self-assembly of silicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Moreover, the sensor’s structural design is critical to improving its linearity and pressure sensing range. Previously, micropatterned , and porous microstructures have been effectively employed to enhance the sensing performance of the tactile sensor. The interlocked structures are widely adopted in micropatterned sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the sensor’s structural design is critical to improving its linearity and pressure sensing range. Previously, micropatterned , and porous microstructures have been effectively employed to enhance the sensing performance of the tactile sensor. The interlocked structures are widely adopted in micropatterned sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The development of flexible electronics has further increased the sensitivity and sensing range of flexible sensors, which can sense external stimuli and convert external mechanical strains into visual electrical signals. Flexible sensors are already widely used in various intelligent devices such as soft robots, electronic skins, and personalized medicine. Materials commonly used for flexible sensors include polydimethylsiloxane, polyurethane, and hydrogels. Compared to other materials, hydrogels have a higher water content and can mimic the stretchable, mechanical, and optical properties of natural soft tissue, making them suitable for a wider range of applications. , Therefore, it is particularly important to develop hydrogel sensors with high performance, high conductivity, and multifunctionality.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies reported that the bending condition of CDBD could affect the discharge [28]. The wearable plasma source was proposed which could be used to treat the large area with irregular shapes [29][30][31]. However, the areas that do not need to be treated still should be driven by the power supply, leading to the high demand for the driven source.…”
Section: Introductionmentioning
confidence: 99%